2013
DOI: 10.1136/jnnp-2012-304038
|View full text |Cite
|
Sign up to set email alerts
|

An 18-year follow-up of seizure outcome after surgery for temporal lobe epilepsy and hippocampal sclerosis

Abstract: MTLE/HS surgery is able to keep patients seizure free for almost up to two decades. Removal of the neocortex besides the mesial portion of the temporal lobe does not lead to better chances of seizure control. These findings are applicable to the typical unilateral MTLE/HS syndrome and cannot be generalised for all types of TLE. Future longitudinal randomised controlled studies are needed to replicate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 32 publications
8
48
1
6
Order By: Relevance
“…Regarding seizure control, a long term follow up confirms the excellent results of this technique 3,6 .…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Regarding seizure control, a long term follow up confirms the excellent results of this technique 3,6 .…”
Section: Resultssupporting
confidence: 61%
“…This study identified the cortical projection of the inferior choroidal point as an excellent guide to reach the temporal horn in a safe and non traumatic way 3,6,20 . It allows the surgeon to limit the corticectomy while maximizing exposure of the amygdala and hippocampus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies using a variety of methods following excision for HS found a probability of seizure freedom of 0.609 and 0.6410 at 5 years and 0.439 and 0.6511 at 10 years and beyond; however, numbers were small, and two used questionnaires years after surgery 9 10. It is likely that our results of people with temporal excision (75% had HS) are lower because of our practice of prospectively obtaining contemporaneous outcome data each year.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, seizure semiology imposes exclusion of a rolandic or insular epileptogenic zone. Dysplastic cerebellar epilepsy shares with temporal lobe epilepsy due to hippocampal sclerosis and some other syndromes the clinical scenario of a high degree of medical intractability but also optimal rates of surgical control [37]. Prognosis seems to be excellent if complete tumor resection is achieved, with total seizure control in 100 % of the patients reported.…”
Section: Discussionmentioning
confidence: 91%